Pengaruh Citra Rasa dan Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Hilande Koffie Medan - Meisya Yusrilia; Arman Syukur Zai; Rolinda Roito Sinaga; Bayu Teta (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This research aims to analyze the effect of taste and service quality on customer satisfaction at Hilande Koffie Medan. As the café business continues to grow in urban areas, customer satisfaction becomes a key factor in business sustainability. Hilande Koffie, located in Medan, offers a variety of pastries and beverages that attract many customers, yet some inconsistencies in taste and service have raised concerns. This study uses a quantitative method with a sample of 45 respondents, applying multiple linear regression analysis through SPSS version 25. The results show that both taste and service quality have a positive and significant effect on customer satisfaction, either partially or simultaneously. The coefficient of determination (Adjusted R²) shows that 65% of the variation in customer satisfaction can be explained by the two independent variables. The findings suggest that maintaining consistency in taste and improving staff professionalism are crucial in enhancing overall customer experience. Therefore, Hilande Koffie is recommended to continuously evaluate and improve both aspects to increase customer satisfaction and loyalty.